2017
DOI: 10.2109/jcersj2.16199
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of resistance to fragmentation of injectable calcium-phosphate cement paste using X-ray microcomputed tomography

Abstract: Property of resistance to fragmentation of injectable calcium-phosphate cement (CPC) pastes was evaluated. CPC pastes are widely used as bone fillers due to their biocompatibility and osteoconductivity. However, the potential for fractures due to the formation of voids and cracks in the CPC, called "fragmentation," reduces the biomechanical strength of CPCs. To develop new CPCs that do not exhibit fragmentation, a method for assessing the presence or absence of fragmentation is required. For in vitro evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…One approach to reduce the setting time is to increase the amount of Na 2 HPO 4 in the mixture. Nagata et al [ 20 ] reported that Na 2 HPO 4 plays a role in shortening the setting time of cement paste; however, it also decreases the compressive strength. Thus, it is necessary to balance the material properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach to reduce the setting time is to increase the amount of Na 2 HPO 4 in the mixture. Nagata et al [ 20 ] reported that Na 2 HPO 4 plays a role in shortening the setting time of cement paste; however, it also decreases the compressive strength. Thus, it is necessary to balance the material properties.…”
Section: Resultsmentioning
confidence: 99%
“…To prepare the mixing solution, 2.5 g of disodium hydrogen phosphate (Na 2 HPO 4 ), 1.0 g of sodium alginate (C 6 H 7 O 6 Na) n ) and 1.5 g of citric acid anhydride (C 6 H 8 O 7 ) were added in this order to 95 g of pure water. The role of each component is as follows: disodium hydrogen phosphate shortens the setting time, sodium alginate enhances the anti-washout property, and citric acid anhydride improves the dispersibility of β-TCP, to improve the consistency of the final cement [ 20 ]. The pH of the solution was adjusted to 7.0 using NaOH solution.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, 10 g of commercially available b-TCP powder (b-TCP-100, Taihei Chemical Industrial Co. Ltd, Japan) was placed in a 3000 ppm 40 cm 3 IP6 solution in a zirconia pot. According to a previous report, 13 the amount of IP6 absorbed on b-TCP powder was determined to be 0.5 mg g À1 under these surface modification conditions. Then, the mixture was simultaneously ground and its surface modified with IP6 using a planetary ball mill (Pulverisette 6, Fritsch Japan Co. Ltd, Japan) in a ZrO 2 pot with 180 g of ZrO 2 beads with a diameter of 2 mm at 300 rpm for 3 h. After ball milling, the resulting slurry was filtered and freeze-dried for 24 h to yield b-TCP powders surface-modified with IP6 (hereafter referred to as IP6/b-TCP powder).…”
Section: Preparation Of Starting Cpc Powdersmentioning
confidence: 89%
“…9 As given in Table 1, the role of each component is as follows: (i) citric acid anhydride binds to Ca 2+ ions in b-TCP, and negatively charging the particles improves the dispersibility of b-TCP to improve dispersion by repulsion between particles, (ii) disodium hydrogen phosphate converts b-TCP to HAp increasing compressive strength and shortening setting time, and (iii) sodium alginate binds to Ca 2+ ions in b-TCP and gelatinizes to inhibit disintegration. 13 The solution was adjusted to pH 7.0 with NaOH solution, and all reagents (Wako Pure Chemical Industries, Ltd, Japan) were used as received, without requiring further purification.…”
Section: Preparation Of the Mixing Liquid For Cement Pastesmentioning
confidence: 99%
See 1 more Smart Citation